MEH-PPV organic material as saturable absorber for Q-switching and mode-locking applications. Issue 8 (3rd May 2020) - Samsamnun, F. S. M.; Zulkipli, N. F.; Majid, W. H. A.; Khudus, M. I. M. A.; Shuhaimi, A.; Rosol, A. H. A.; Arof, H.; Yasin, M.; Harun, S. W.
ABSTRACT: Q-switched and mode-locked pulse generation in Erbium-doped fiber lasers (EDFLs) are demonstrated using Poly [2-methoxy-5-(2-ethylhexyloxy)-1, 4-phenylenevinylene] (MEH-PPV) organic semiconductor material as a saturable absorber (SA) for the first time. The MEH-PPV was prepared in the form of a thin film having a modulation depth of 12% and saturation intensity of 40 MW/cm 2 . The SA was placed in a laser cavity to produce a stable Q-switched operating at 1564.0 nm. The maximum repetition rate of 78.62 kHz, minimum pulse width of 3.54 µs and maximum pulse energy of 59.45 nJ were attained at 125.2 mW pump power. On the other hand, by incorporating an additional 100 m long single mode fiber, the mode locked EDFL self-started as the pump power was raised above 125.2 mW. The soliton pulse was obtained due to the enhancement of the nonlinearity in the cavity. The mode-locked laser operated at 1568.5 nm with a fixed repetition rate of 1.859 MHz and pulse width of 2.97 ps.